Pemasaran Destinasi Pariwisata Melalui Digitalisasi Marketing Berbasis Community Based Tourism (CBT) Di Desa Wisata Tipang Kecamatan Bakti Raja Kabupaten Humbang Hasundutan - Lydia De Vega (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2022)
Tourism potential needs to take advantage of digital marketing so that all attractions and tourist attractions are increasingly known to all levels of society. The participation of local communities is very necessary, therefore, digitalization of community-based tourism (CBT)-based marketing is needed. Descriptive qualitative research methods, to obtain data used questionnaires and interviews. From this research, it was found that digital marketing has been implemented well. Information and other things about tourism potential can be accessed by anyone. Tourist visits can book tour packages digitally. Likewise with the participation of the community in the local village.